Handbook of industrial biocatalysis. - Hou, Ching T. (Ching-Tsang), 1935- (Boca Raton : CRC, 2005)
Until now, no comprehensive handbook on industrial biocatalysis has been available. Soliciting chapters on virtually every aspect of biocatalysis from international experts most actively researching the field, the Handbook of Industrial Biocatalysis fills this need. The handbook is divided into three sections based on types of substrates. The first section describes the newest biotechnology and bioprocesses for producing industrial products from hydrophobic substrates such as oils and fats. The discussion of biocatalysis covers single and multiple catalytic reactions involved in the creation of products as well as molecular manipulation of enzymes and product recovery. The products include healthy food, nutritional supplements, nutraceuticals, specialty chemicals, surfactants, biopolymers, and antimicrobial agents. The second section covers the production of value-added products from carbohydrate substrates. The scope of this section includes ethanol production, oligosaccharides and glycosides, utilization of hemicelluloses, and carbohydrate-active enzymes. The third section is dedicated to other potential industrial applications such as bioelectrocatalysis for synthesizing chemicals, fuels, and new drugs. The authors explore novel nutrition delivery systems, green chemistry, and the industrial applications of extremophiles. The organizer of several annual worldwide symposia on biocatalysis, editor Ching T. Hou has compiled a cornerstone reference for scientists in academic, industrial, and government research institutes, as well as for graduate-level students involved in biosciences, chemical engineering, biotechnology, microbiology, oil and colloid chemistry, and food chemistry.